Drainage-only strategy on weekend for endoscopic retrograde cholangiopancreatography on the risk of procedure-related adverse events: a prospective observational study - Eunae Cho; Se Woo Park; Kyong Joo Lee; Da Hae Park; Hyewon Cha; Dong Hee Koh; Jin Lee; Chan Hyuk Park (Therapeutic Advances in Gastroenterology)
Background: The feasibility of performing complete endoscopic retrograde cholangiopancreatography (ERCP) for acute cholangitis during weekends or holidays remains controversial due to concerns over increased risks of adverse events (AEs) in off-hour procedures. Objectives: To evaluate whether weekend drainage-only ERCP affects the incidence of AEs compared to standard weekday ERCP, and to identify risk factors for post-ERCP pancreatitis (PEP). Design: Prospective observational study. Methods: Patients with acute cholangitis, diagnosed based on the Tokyo Guidelines 2018 and naïve major papillae, were prospectively enrolled between 2018 and 2023. Patients were categorized into two groups: the “Weekend ERCP” group, in which initial biliary drainage was performed on weekends with subsequent therapeutic ERCP on weekdays, and the “Weekday ERCP” group, in which all procedures were completed during weekdays. The primary outcome was the incidence of PEP; secondary outcomes included overall AEs and risk factor analysis. Results: A total of 1772 patients were included (Weekend group: n  = 148; Weekday group: n  = 1624) in this study. The incidence of PEP was 4.1% in the Weekend group and 4.9% in the Weekday group ( p  = 0.810). Overall AEs occurred in 3.4% and 4.9% of patients, respectively ( p  = 0.540). Multivariable analysis identified age ⩽60 years, female sex, history of acute pancreatitis, difficult cannulation, and endoscopic papillary balloon dilation as independent risk factors for PEP. Timing of ERCP (weekend vs weekday) was not associated with increased risk of PEP. Conclusion: Weekend ERCPs limited to drainage-only strategies are as safe as weekday procedures in terms of AE rates, effectively managing resources and providing timely biliary decompression for acute cholangitis emergencies, although they often require subsequent definitive interventions. Trial registration: The International Clinical Trials Registry Platform (identifier KCT0005950; https://cris.nih.go.kr ).